Pengaruh Penyangraian Dengan Wajan Yang Berbeda Terhadap Kondisi Fisik dan Kualitas Organoleptik Seduhan Bubuk Kopi Liberika Tungkal Komposit(Libtukom) - Ridawati Marpaung; Al Fajri Suriyansah (Jurnal Media Pertanian, 2021)
This study aimed to determine the Effect of roasting with different pans on the organoleptic quality of tungkal composite liberica coffee   brew (Libtukom)”. The expected outcome of this research was to increase the view of traditional coffee powder business actors about the use of a good roasting pan in the roasting process of coffee beans to produce good quality characteristics of coffee powder brewing and to add to the knowledge in the field of processing technology in plantation products. The research was carried out in  Basic Agricultural Laboratory, Batanghari University. A Completely Randomized Design was implemented in as environmental design that used in this study.  The treatment design were roasting with different types of pans, as follows: W1 = Iron skillet, W2 = Aluminum skillet, W3 = Earth skillet (pottery), W4 = Teflon skillet and W5 = Stainless Steel skillet. It was 3 timesrepeatation on each treatment. The results showed that the type of roasting pan had a significant effect on organoleptic quality included color, aroma, taste, bitterness of libtukom coffee powder brewing, but had no significant effect on the preference variables. The highest assessment of the preference variable was found in coffee powder that are roasted using aluminium skillet.